Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300657
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Visuo-Haptic Mismatches in Virtual Reality using the Prediction Error Negativity of Event-Related Brain Potentials

Abstract: Designing immersion is the key challenge in virtual reality; this challenge has driven advancements in displays, rendering and recently, haptics. To increase our sense of physical immersion, for instance, vibrotactile gloves render the sense of touching, while electrical muscle stimulation (EMS) renders forces. Unfortunately, the established metric to assess the effectiveness of haptic devices relies on the user's subjective interpretation of unspecific, yet standardized, questions. Here, we explore a new appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 47 publications
1
33
1
Order By: Relevance
“…Therefore, they were evidently not able to distinguish the mismatched stimuli. This contradicts the findings reported in various other studies concerning mismatched stimuli 76,77 and studies indicating that accurate or logical tactile feedback makes the interaction more realistic compared with illogical tactile feedback 7,78 . However, considering that most of the prior studies that we reviewed provided more discrete visual and haptic interaction compared with this study, our results have gone a step further.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, they were evidently not able to distinguish the mismatched stimuli. This contradicts the findings reported in various other studies concerning mismatched stimuli 76,77 and studies indicating that accurate or logical tactile feedback makes the interaction more realistic compared with illogical tactile feedback 7,78 . However, considering that most of the prior studies that we reviewed provided more discrete visual and haptic interaction compared with this study, our results have gone a step further.…”
Section: Discussioncontrasting
confidence: 99%
“…Even though improved mobile brain imaging methods allow for investigating naturalistic interactions with technical systems in the workplace and everyday settings (Gehrke et al, 2019;Wascher et al, 2020), these new methods likely come with potential changes in the extracted neural parameters (Gramann et al, 2018). Such differences have to be described and embedded in a systematic fashion to allow for understanding the theoretical and methodological framework and to foster convergence with results from standard laboratory protocols, leading directly to the third grand field challenge.…”
Section: Challenge 2: Imaging Methods For Embodied Cognitive Neuroergmentioning
confidence: 99%
“…When defining proxy variables, researchers (i) used previously validated measures when available for theoretical and methodological soundness, such as the Barcelona Music Reward Questionnaire (BMRQ) to measure music reward (in [36]), or (ii) developed new measures as a research contribution. For example, in [26], the authors develop an EEGbased measure for "immersiveness" in VR they demonstrated to be superior to previous measures that required halting immersive VR experiences to ask users about immersion. Researchers also sometimes justified choosing proxies based on available data.…”
Section: 22mentioning
confidence: 99%